2017
DOI: 10.1111/1468-0009.12297
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Care Among Transgender and Gender Nonconforming Adults

Abstract: Transgender and GNC adults face barriers to health care that may be due to a variety of reasons, including discrimination in health care, health insurance policies, employment, and public policy or lack of awareness among health care providers on transgender-related health issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
150
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(173 citation statements)
references
References 29 publications
10
150
1
2
Order By: Relevance
“…24 Transgender people with multiple chronic conditions might be more likely to have an unmet need for caregiving; although 90% of the in-home long-term care are unpaid family or informal caregivers, 25 transgender people experience significant family rejection 23 and less social support. Although all transgender groups had a higher prevalence of no health insurance (largely consistent with a prior study), 26 few differences in preventive care utilization were observed, except for delaying care because of cost compared with CMs. This is consistent with prior research on preventive care in Medicare data 27 and could be attributed to more healthcare use among this group compared with cisgender peers.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…24 Transgender people with multiple chronic conditions might be more likely to have an unmet need for caregiving; although 90% of the in-home long-term care are unpaid family or informal caregivers, 25 transgender people experience significant family rejection 23 and less social support. Although all transgender groups had a higher prevalence of no health insurance (largely consistent with a prior study), 26 few differences in preventive care utilization were observed, except for delaying care because of cost compared with CMs. This is consistent with prior research on preventive care in Medicare data 27 and could be attributed to more healthcare use among this group compared with cisgender peers.…”
Section: Discussionsupporting
confidence: 84%
“…These results differ from a prior estimate using the 2014-2015 BRFSS data that found GNC people reported delaying care because of cost and not having a primary care visit in the last year compared with CFs. 26 Research on how health access and insurance varies over time and place is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Further, these negative consequences for health are likely to be compounded for individuals from multiple minority backgrounds, such as LGBTQ racial/ethnic minorities or LGBTQ women . Transgender people, with their unique health concerns, may also face special health‐related vulnerabilities as a result of discrimination, including social and economic vulnerabilities that increase health risks . These effects are particularly alarming given that LGBTQ people are significantly less likely than non‐LGBTQ people to have health insurance and therefore may have less access to medical care that could mitigate the adverse health consequences of discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…18,[25][26][27][28][29][30] Transgender people, with their unique health concerns, may also face special health-related vulnerabilities as a result of discrimination, including social and economic vulnerabilities that increase health risks. 31,32 These effects are particularly alarming given that…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation